Correlation of Modified Computed Tomography Severity Index with Ranson’s Criteria in Assessing Severity of Acute Pancreatitis - S Mangalanandan; Divya Ann Thomas; Geena Benjamin (International Journal of Anatomy Radiology and Surgery, 2021)
Introduction: Acute Pancreatitis (AP) is an illness which results in increase in morbidity and mortality when there is a delay in diagnosis and there are false results. Various scales help in making early and accurate diagnosis of AP and predict prognosis. Validity of these scales needs to be studied and compared. Balthazar score and Ranson’s criteria have been commonly used. Modified CT score’s usefulness need to be studied as it involves only CT and their early detection will help in reducing the morbidity (reducing the residual damage) and mortality. Aim: To determine validity of modified Computed Tomography Severity Index (CTSI) and Ranson’s score in assessing severity of AP and study their correlation. Materials and Methods: This is an observational study among 39 patients with AP. Ranson’s score and Modified CT index was calculated and actual outcome of the disease was observed. Results: Ranson’s Score and Modified CTSI were strongly correlated with rho value of 0.912 and p-value of <0.001. Sensitivity and specificity of Ranson’s criteria in predicting the actual outcome of the disease is 80% and 83.3%, respectively. Sensitivity and specificity of Modified CT criteria in predicting the actual outcome of the disease is 93.33% and 54.17%, respectively. Conclusion: From the results of this study, it is evident that Modified CT index is more sensitive than Ranson’s score, but less specific.